Pomfret (paplet) Fish - Mumbai Archive Project Team (Jio Institute, 2024)
Due to its high demand and limited supply, pomfret (paplet) is typically the priciest fish available for purchase. Pomfret typically live in deeper waters, which makes them more difficult to catch and accounts for their higher price.